PENGELOLAAN FASILITAS OUTDOOR ACTIVITIES BAGI WISATAWAN DI WATER FRONT CITY SIAK SRI INDRAPURA - Suci Sutriani; Andri Sulistyani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Tourism facilities can be interpreted a facility and infrastructure that must be provided by the manager to the needs of tourists. This study was conducted in Water Front City of village of Rempak subdistrict, Siak District, Siak Regency. This research aims to know how to manage Outdoor Activities facilities for tourists in Water Front City Siak Sri Indrapura. This research uses quantitative descriptive methods to process the data obtained in the field through interviews, observations, documentation, and questionnaires all information collected and studied so that it becomes a unified whole ( Sugiono, 2000). As for the sample in the study of 100 respondents, the determination of respondents with Accidental Sampling. The data collection techniques used are observations, interviews, documentation, and questionnaires, using the Likert scale as a measuring instrument. Based on the results of the research that has been done, the management of Outdoor Activities for tourists in Water Front City Siak Sri Indrapura with Sub variables stay, eat & drink, service to the desires of the tourists. Keywords: Facilities Management, Outdoor Activites, Water Front City